2001
DOI: 10.1080/104732201753214170
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Environmental Quality in Six Commercial Office Buildings in the Midwest United States

Abstract: The aims of this study were to characterize physical, mechanical, and environmental factors influencing indoor environmental quality (IEQ) in commercial office buildings; document occupant perceptions and psychosocial attributes; and evaluate relationships among these parameters. Six large office buildings in metropolitan areas were selected in Iowa, Minnesota, and Nebraska. Comprehensive sampling was conducted over one week in each building, during all four seasons. This paper presents the study methods and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 20 publications
5
73
1
4
Order By: Relevance
“…However, before generalising it is prudent to examine potentially confounding factors. Many contributors to the SBS research literature have emphasised the inclusion of psycho-social or work-related factors when investigating sex differences [30,37,46,61]. That is, the frequently reported female occupants' health symptoms or complaints could be influenced by personal or occupational characteristics unrelated to indoor environment such as job-related stress, lack of control of work, low job pride resulting from low position within the organisational hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…However, before generalising it is prudent to examine potentially confounding factors. Many contributors to the SBS research literature have emphasised the inclusion of psycho-social or work-related factors when investigating sex differences [30,37,46,61]. That is, the frequently reported female occupants' health symptoms or complaints could be influenced by personal or occupational characteristics unrelated to indoor environment such as job-related stress, lack of control of work, low job pride resulting from low position within the organisational hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds et al 13) reported that geometric mean concentrations of HCHO and CH 3 CHO in six commercial office buildings ranged from 5.0-13.3 µg/m 3 and 3.0-7.5 µg/m 3 , respectively. Also, Ikeda et al 4) reported that the mean concentrations of HCHO and CH 3 CHO in 53 rooms in a newly built condominium were 83.4 ± 5.6 µg/m 3 and 46.6 ± 3.2 µg/m 3 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Typical levels of CO in offices are between 0-5 ppm [Illinois Department of Public Health 2011]. Average CO levels found in a study of six office buildings located in the United States ranged from 1-1.5 ppm [Reynolds et al 2001]. Another study of 56 European office buildings reported average CO levels that ranged from 0.5-1.9 ppm [Bluyssen et al 1996].…”
Section: Real-time Monitoring Of Co 2 Co Temperature and Relativementioning
confidence: 99%